Magnesium Oxide (MgO) as a Sustainable Catalyst for Biodiesel Production from Waste Cooking Oil: A Comparative Study with KOH - Eladeb, Aboulbaba (Engineering, Technology & Applied Science Research, 2024)
The present study investigates the efficiency of magnesium oxide (MgO) as a heterogeneous catalyst in the production of biodiesel from waste cooking oil (WCO), putting an emphasis on its environmental benefits, cost-effectiveness, and operational efficacy. Through a series of experiments, we optimized the reaction conditions, including catalyst concentration, reaction temperature, and ethanol to WCO molar ratio, to achieve a high biodiesel yield. The results indicate that an optimal MgO concentration of 3 wt%, a reaction temperature of 65 °C, and a molar ratio of 9:1 result in the highest biodiesel production efficiency. Additionally, MgO demonstrated significant reusability without a decrease in performance, underscoring its economic and environmental advantages. Comparative analysis revealed that MgO outperforms conventional KOH catalysts in terms of yield, purity, and sustainability. Our study suggests future research directions, including the optimization of MgO preparation methods and the exploration of co-catalyst systems to further enhance biodiesel production from WCO. This research contributes to the development of sustainable biodiesel production methods, aligning with global energy and environmental goals.